Colossal grain boundary strengthening in ultrafine nanocrystalline oxides - Muche, Dereck N.F.; Drazin, John W.; Mardinly, John; Dey, Sanchita; Castro, Ricardo H.R. (Materials letters, 2017)
One of the most classic size-effects in materials is the increase in the strength and hardness as the grain size decreases. However, a practical low size limit for this so-called grain boundary strengthening has been extensively reported for both metals and ceramics. Here, it is demonstrated that this limit is not observed in fully dense nanocrystalline magnesium aluminate, where hardness increases from 17.2 to 28.4GPa (surpassing sapphire hardness) when grain sizes are refined from 188nm to 7.1nm, respectively. The increasing trend is proportional to the square root of the grain size, following the Hall-Petch relationship, reassuring that common weakening mechanisms described in nanocrystalline metals might not be present in ceramics. To achieve such small grain sizes in fully dense ceramics, a new processing technique is introduced, Deformable Punch Spark Plasma Sintering, DP-SPS, in which nanoparticles are sheared under high pressures (~2GPa) during densification at moderate temperatures (720–870°C). This inhibits grain growth due to the low processing temperatures and destabilizes/eliminate isolated residual pores, known to detrimentally affect mechanical behavior of ceramics. Noticeably, the sintered material showed high transparency in the visible spectrum, being reported as one of the hardest transparent oxide material to date. •Fully dense nanocrystalline transparent magnesium aluminate was produced.•Unprecedented hardness of 28.4GPa was observed for 7.1nm grain size.•Hall-Petch relation held true from micro to nano-sizes.•Mechanism of densification relates to punch deformation during sintering.